THE STRATEGY FOR OPTIMIZING PURCHASE INTENTION OF ELECTRIC VEHICLES MEDIATED WILLINGNESS TO PAY - Harno, Rinto; Hasibuan, Putri Septi Naulina; Rinawati, Liya (Transpublika Publisher, 2023)
Currently, many people have the purchasing power to buy Battery Electric Vehicle (BEV) cars, making them a popular trend in the automotive industry due to their ability to reduce air pollution in the long term. This research aims to identify important factors that influence the purchasing decision of BEV cars. The study employed a quantitative research design, where data were collected through questionnaires distributed to potential BEV car users. Data analysis was done using a multiple regression model. The results showed that there was an influence between Cost, Technology and Macro Level on Purchase Intention either partially or simultaneously. To increase BEV car purchases, strategies should be focused on minimizing the production cost of the cars, introducing modern yet user-friendly technology, and promoting the benefits of BEV cars over conventional ones. This can help shift people's attitudes and behaviors towards BEV cars.